WATER POLLUTION CONTROL POLICY IN NEPAL AND INDONESIA - Qasthary, Auzan; Muttaqien, Al (Jurnal Sains Riset, 2022)
Water is a fundamental aspect of Indonesia's natural resources that must be utilized to the greatest extent possible for the benefit of the people. This indicates that the use of water for various purposes and interests must be done with caution, with regard to the interests of present and future generations in mind. Most water sources in Nepal have become polluted due to fast population growth. Water quality problems caused by physical and chemical factors have a big effect on public health when the concentrations are high. In this study, normative legal research methods are used, where library materials are basic information that is delegated and additional information is available. The conclusion of this research is that Nepal's constitution is founded on and approved by law, and it governs political, economic, and social connections as well as other rights such as land ownership. Changes in political systems and power relations result in changes in laws, decision-making authorities, and institutions, which impact water rights interactions. As an archipelagic country with a sea that encompasses two-thirds of its national territory, the world's second longest coastline, and is also known as a maritime country, Indonesia bears a significant obligation to safeguard its seas from water pollution.Keyword: Water Pollution, Policy